2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35573
|View full text |Cite
|
Sign up to set email alerts
|

WIP: Teacher Leader Engineering Network (TaLENt): A Collective Impact Model for K-12 Engineering Teacher Leaders

Abstract: leads the NanoEnvironmental Engineering for Teachers program. In this capacity, she guides Houston area secondary science teachers in weekly meetings on Rice's campus to "best practices" in educational pedagogy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The High-Quality Engineering Guidebook includes five criteria for teaching engineering design at each school level (elementary, middle, and high) framed through culturally relevant pedagogy. Our 2019 paper, published in the American Society for Engineering Education (ASEE) conference proceedings, provides in-depth details on developing the High-Quality Engineering Guidebook [15]. This qualitative research aimed to assess the effectiveness of four TaLENt fellows, who are school-based teacher leaders, as in-school change agents for educators who are inexperienced in engineering design.…”
Section: Purpose Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The High-Quality Engineering Guidebook includes five criteria for teaching engineering design at each school level (elementary, middle, and high) framed through culturally relevant pedagogy. Our 2019 paper, published in the American Society for Engineering Education (ASEE) conference proceedings, provides in-depth details on developing the High-Quality Engineering Guidebook [15]. This qualitative research aimed to assess the effectiveness of four TaLENt fellows, who are school-based teacher leaders, as in-school change agents for educators who are inexperienced in engineering design.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…There is substantial evidence that most K-12 science and math teachers who aim to incorporate engineering design processes into their courses acquire these skills through extracurricular professional development (PD) programs or self-directed learning [1][2][3][4]. Research has shown that PD programs are valuable in increasing teachers' engineering self-efficacy and the likelihood of implementing engineering processes in the classroom [5][6][7]. These programs offer flexibility in introducing engineering design to teachers in diverse formats (e.g., in-person versus virtual) [8], using various theoretical frameworks [9].…”
Section: Introductionmentioning
confidence: 99%
“…While other research studies did include a variety of populations, such as women in EL, undergraduate and graduate students, teaching assistants, faculty, seniors, and students in teams, those studies fell under different clusters as the research had a stronger focus on other aspects of EL development, not the population's experience or needs specifically. The only cluster that focused on students' pre-college academic preparation was a small cluster of papers that explored a model for developing Teachers as Leaders in K-12 to bolster student STEM leadership [27]. Another small cluster of papers focused on the Oral History of Women leaders in STEM.…”
Section: Rq1: What El Topics Has the Research Published At Asee Confe...mentioning
confidence: 99%
“…Few studies focused on engaging pre-college students around the importance of EL skills for their academic and industry careers. Those studies that did focus on pre-college students, e.g., [27], largely examined models for supporting teachers in their leadership development and instruction in the Teachers as Leaders cluster. This may reflect how EL is a relatively new body of knowledge, but perhaps also a disconnect between ABET requirements and pre-college requirements for engineering education [8].…”
Section: Rq2: Are There Gaps In the El Research Published At Asee Con...mentioning
confidence: 99%